نظام النقابات وحل النزاعات في التشريع الكويتي دراسة تحليلية في ظل المواثيق والاتفاقيات الدولية - أصيمع، حمد سالم (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2021)
The research aims to uncover the legal framework for organizing trade unions, their functions and the principles of union actions. The study also shows the role played by international conventions and Kuwaiti legislation in overcoming legal problems resulting from union disputes. It also shows the peaceful and coercive means to settle union disputes. In order to achieve this, the researcher collected data and information on the subject through Kuwaiti regulations and laws, making use of Egyptian laws as one of the most prominent and oldest laws among the Arab countries. Using the analytical descriptive method to analyse Kuwaiti and Egyptian laws, as well as the comparative approach to comparing legal texts on legal disputes in Kuwaiti and Egyptian legislation and then the historical method to the history and development of trade unions in Kuwait and Egypt. The research examined the concept, origin and development of trade unions, the legal framework for trade union work, the management of trade union work, the rights of workers, the bodies for the settlement of trade union disputes and the peaceful and coercive means for the settlement of labour disputes. The research concluded that, whatever its pattern, a trade union has the task of defending its members' interests, whether material or moral. Professional problems for its members remain in its humanitarian work, and there are many peaceful and coercive ways and means to settle union disputes. The research recommended that special attention should be paid to trade union freedoms in order to exercise their role in the settlement of labour union disputes, as well as to amending Kuwaiti trade union dispute settlement laws so that the dispute could be resolved expeditiously.